Potentially Toxic Concentrations of Synthetic Pyrethroids Associated with Low Density Residential Land Use - Marshall, Stephen; Sharley, David; Jeppe, Katherine; Sharp, Simon; Rose, Gavin; Pettigrove, Vincent (Frontiers in Environmental Science, 2016)
Trace organic compounds associated with human activity are now ubiquitous in the environment. As the population becomes more urbanised and the use of pesticides and person care products continues to increase, urban waterways are likely to receive higher loads of trace organic contaminants with unknown ecological consequences. To establish the extent of trace organic contamination in urban runoff, concentrations of emerging chemicals of concern were determined in sediments from 99 urban wetlands in and around Melbourne, Australia between February and April, 2015. As a preliminary estimation of potential risks to aquatic biota, we compared measured concentrations with thresholds for acute and chronic toxicity, and modelled toxic units as a function of demographic and land use trends. The synthetic pyrethroid insecticide bifenthrin was common and widespread, and frequently occurred at concentrations likely to cause toxicity to aquatic life. Personal care products DEET and triclosan were common and widely distributed, while the herbicides diuron and prometryn, and the fungicides pyrimethanil and trifloxystrobin occurred less frequently. Toxic unit modelling using random forests found complex and unexpected associations between urban land uses and trace organic concentrations. Synthetic pyrethroid insecticides were identified as emerging compounds of concern, particularly bifenthrin. In contrast with previous surveys, the highest bifenthrin concentrations were associated with lower housing and population density, implicating low-density residential land use in bifenthrin contamination. We discuss the implications for pesticide regulation and urban wetland management in a global context.